Analysis and Design of Obstacle Avoidance on Robot Detection of Pipe Cracked - Yudha Wira Pratama; Tresna Dewi; Yurni Oktarina (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
Pipe robot is a robot capable of moving inside the pipe. The function of the pipe robot is to monitor pipe defects. The pipe robot is designed to move steadily in the center position inside the pipe. HCSR-04 distance sensor required input to give distance value to the microcontroller so that robot keep running stable and balance, for movement of the robot using DC motor. This robot is made with the aim to move autonomously following the pipeline in detecting pipe cracks. Programming on this robot using Artificial Neural Network algorithm with the Backpropogation method of network structure, consist of 3 input layer, 3 output layer, and 20 hidden layers. Conducted experiments on inputs, hidden layers, and outputs with varying amounts to obtain robust network structure of efficient and precise movement of robots in detecting pipe cracks. The result of movement of the robot in the application of Artificial Neural Network algorithm with Backpropagation method is able to move well and more stable. In this case, it uses 2 ultrasonic sensors and 2 motor outputs. The average robot speed movement is 10 cm/sec.